FEMALE EXPRIENCES IN DIFFERENT CULTURAL BACKGROUNDS: GYNOCRITICISM ON SHORT STORIES OF FIVE CONTINENTS - Evi Jovita Putri (Vivid: Journal of Language and Literature, 2014)
In this article the author wants to show the experiences of women from various backgrounds , namely China , America , Australia , Europe , and Africa through five different stories. The author also looks at the culture of patriarchy underlying these writings. In this study, the author uses the theory of gynocriticism of Elaine Showalter , who suggested the importance of discussing the works of women from female perspectives. From this study, the authors concluded that women writers are trying to present that being a woman was difficult , both as a young woman, as well as middle-aged . Proven by the failure of male figures in the short stories to understand the thoughts and desires of women Furthermore, the author concludes that patriarchal environments create obstacles for women to be heard or understood. Keywords : short stories , works of women, world literature, feminist criticism